National plumbing codes handbook - Woodson, R. Dodge (McGraw-Hill, 1998)
A comprehensive reference to the three major plumbing codes in use today. The book shows how to apply sound plumbing principles to code requirements, aiming to provide an understanding of what must be done to comply with plumbing code regulations and pass inspection.